Monetary Policy Contagion in the West African Monetary Zone. Issue 4 (November 2019) - Tule, Moses K.; Ajilore, Taiwo; Ujunwa, Augustine
The study utilized quarterly time series data for Nigeria and three selected West African Monetary Zone (WAMZ) countries for the period 1980–2016 to verify whether monetary policy shocks emanating from Nigeria are an important source of macroeconomic fluctuations in WAMZ economies. The study complemented the Global vector autoregressive method with the Diebold–Yilmaz (2009) connectedness weights computation for the analysis. Inferences from generalized impulse response function (GIRF) analysis indicated that an unanticipated Nigerian monetary policy shock depreciates the Nigeria–USA exchange rate, stimulates growth, decelerates inflation and expands the money stock in the short run for Nigeria. In Ghana, Nigeria's monetary policy shocks similarly depreciates the exchange rate, slows growth with high inflationary impact in the short run. In the Gambia, unanticipated shocks emanating from Nigeria strengthens the Gambia–USA exchange rate, depresses growth and inflationary pressures. Sierra Leone shares the appreciation of its currency with the Gambia, in addition to an economic expansion and rising inflation. Money supply also increases to accommodate the expanding demand. These results validated the thesis that there exist considerable geographical linkages within the WAMZ regions through which macroeconomic fluctuations are transmitted. For policy, monetary authorities in the region should collectively address the question of how to stabilize the economy in response to monetary policy shocks emanating from Nigeria. JEL Codes: E52, E32, E65, F02